Implications of the Deprivation of Land Rights in the Public Interest on Citizens' Property Rights - Belliana Herlina; Shafa Athaya; Vannestian Marhein (CV. Rayyan Dwi Bharata, 2023)
The purpose of writing this paper is to explain the regulations for implementing land acquisition for the public interest, which in writing this paper uses case studies on land acquisition for the new State Capital in East Kalimantan. Through writing this paper, the author tries to explain about the form and mechanism of compensation to the aggrieved party due to the occurrence of land acquisition based on Law no. 2 of 2012. The method used is normative juridical analysis. With the conclusion that the process of implementing land acquisition for public purposes is carried out by the Head of the Regional Office of the National Land Agency and the Head of the Land Office after receiving an assignment from the Head of the Regional Office of the National Land Agency with all duties and responsibilities starting from the implementation stage to the delivery of results with a term the time specified in the Land Acquisition Law for the public interest and its implementing regulations. 2. Assessment of the amount of compensation in the procurement of land for the public interest is carried out plot per plot of land, including: land, above-ground and underground space, buildings, plants, objects related to land, and other losses that can be assessed.